Education intervention model on clean and healthy living habits among mothers having children less than 2 years of age border in remote areas, Indonesia - Gustina, Mely; Ali, Haidina; Bathari, Rosalia Rina; Hendryani, Atika; Rahmawati, Ullya (Malahayati International Journal of Nursing and Health Science, 2023)
Background: Stunting in toddlers reflects a failure to grow due to nutritional deficiencies. Repeated exposure to fecal pathogens, especially prevalent in areas where open defecation practices exist, can lead to diarrhea, hindered growth, health issues, and irreversible developmental impairments.Purpose: To determine the effectiveness of Agamis Sistematis Interaktif Kreatif/ASIK (Religious, Systematic, Interactive, Creative) education model (focusing on water, sanitation, and hygiene) on clean and healthy living habit (CHLH) among toddlers at risk of stunting in the remote border areas of Enggano Island, Bengkulu Province in 2023.Method: The researcher employed a non-equivalent control group design, also known as a pre-test post-test control group design, for the experimental and control groups. This research involved a sample of 60 mothers having children less than 2 years of age, comprising 30 in the intervention group and 30 in the control group. Data collection utilized a questionnaire. Univariate and bivariate data analysis was conducted using the paired t-test statistical analysis. The results of this study revealed a difference in the mean values between the experimental and control groups concerning WAZ (weight-for-age z-scores), with values in the experimental group pre=72.7000, post=75.2667, and the control group pre=76.8167, post=78.4167.Results: The research findings indicated a difference in CHLH between the treatment and control groups (ρ=0.000, ρ<0.05). The ASIK education model on CHLH among toddlers at risk of stunting is effectively applicable in the remote border areas of Enggano Island, Bengkulu Province in 2023.Conclusion: Government support in the form of budget allocation is crucial for the sustainability of continuous education aimed at stunting prevention in village communities.